Model Pengembangan Kurikulum Fikih Kebangsaan di Ma’had Aly Lirboyo: Konstruksi Epistemologi dan Implementasinya dalam Menjawab Tantangan Global - Muhammad Zainul Millah (CV. Gerasi Insan Nusantara, 2026)
Indonesia is a nation characterized by rich racial, cultural, and religious diversity. Consequently, a comprehensive understanding of national fiqh (fiqh al-kebangsaan) is paramount to sustaining the country's existence. Ma’had Aly Lirboyo has demonstrated a firm commitment to preserving the Unitary State of the Republic of Indonesia (NKRI) by establishing national fiqh as its core academic concentration. This study aims to investigate the development of the national fiqh curriculum at Ma’had Aly Lirboyo and analyze it through the lenses of both modern and Islamic curriculum development theories.This study employed a qualitative approach with a case study design. Data were gathered through a textual analysis of the Fikih Kebangsaan books, curriculum blueprints, and field data obtained through in-depth interviews and observations. The collected data were analyzed through reduction, data display, and conclusion drawing, with validity ensured via data triangulation. The findings indicate that the Fikih Kebangsaan curriculum aligns with the core principles of modern curriculum development, namely relevance, flexibility, practicality, and effectiveness. Specifically, the model demonstrates relevance by aligning Islamic law with the multi-religious and political realities of Indonesia. Its flexibility allows the curriculum to adapt to the diverse educational backgrounds of students. Practicality is achieved through a structured broad-field curriculum that integrates classical texts (turath) with contemporary social issues. Effectiveness is proven by its operationalization through collective ijtihad (baḥtsul masail) to formulate clear national legal consensus. Developed through a mechanism of collective ijtihad, the curriculum also embodies the principles of Islamic curriculum development by effectively adapting to contemporary Islamic realities in Indonesia while firmly anchoring itself in the turath (classical Islamic texts) tradition. These findings recommend the Fikih Kebangsaan model as an alternative Islamic education curriculum capable of bridging religious norms and state regulations within the Indonesian context.